2009
DOI: 10.1007/s10565-009-9137-7
|View full text |Cite
|
Sign up to set email alerts
|

Prooxidative effects of green tea polyphenol (−)-epigallocatethin-3-gallate on the HIT-T15 pancreatic beta cell line

Abstract: Epigallocatechin-3-gallate (EGCG) is the main polyphenolic constituent in green tea and is believed to function as an antioxidant. However, increasing evidence indicates that EGCG produces reactive oxygen species (ROS) and subsequent cell death. In this study, we investigated the prooxidative effects of EGCG on the HIT-T15 pancreatic beta cell line. Dose-dependent cell viability was monitored with the cell counting kit-8 assay, while the induction of apoptosis was analyzed by a cell death ELISA kit and comet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 35 publications
5
54
0
1
Order By: Relevance
“…Although ROS act as signal transducers, when accumulated in cells in the form of hydrogen peroxide, superoxide, and hydroxyl radicals, ROS are considered essential regulators of aging and have been reported to be a key element in the apoptosis of yeast (48)(49)(50). The synergistic interactions observed in this study indicate a probable prooxidant activity of flavonoids, which may be responsible for the induction of transcription factors associated with apoptosis and related to increased levels of proapoptotic proteins, mitochondrial injury, and ROS generation, as well as accelerated oxidative damage to DNA, proteins, and carbohydrates in vitro (51)(52)(53).…”
Section: Figmentioning
confidence: 62%
See 1 more Smart Citation
“…Although ROS act as signal transducers, when accumulated in cells in the form of hydrogen peroxide, superoxide, and hydroxyl radicals, ROS are considered essential regulators of aging and have been reported to be a key element in the apoptosis of yeast (48)(49)(50). The synergistic interactions observed in this study indicate a probable prooxidant activity of flavonoids, which may be responsible for the induction of transcription factors associated with apoptosis and related to increased levels of proapoptotic proteins, mitochondrial injury, and ROS generation, as well as accelerated oxidative damage to DNA, proteins, and carbohydrates in vitro (51)(52)(53).…”
Section: Figmentioning
confidence: 62%
“…Such a ⌬m collapse can lead to transient pore openings in the mitochondrial membrane and the release of proapoptotic factors into the cytosol (50,54). This fact can be explained by the ability of flavonoids to exhibit a prooxidant activity (52,53) that favors increased intracellular levels of hydroxyl radicals that lead to mitochondrial membrane damage. Hwang et al (55) showed that the flavonoid amentoflavone promotes mitochondrial dysfunction in C. albicans strains due to increased levels of ROS.…”
Section: Figmentioning
confidence: 99%
“…We have shown previously that the antioxidants NAC and ALA protect pancreatic β-cells and MC3T3-E1 osteoblastic cells against oxidative stress as shown by a reduction in ROS generation and apoptosis. [14][15][16]19,31) These findings indicate that apigenin can function as an antioxidant and thereby protect pancreatic β-cells from dRib-induced oxi- dative cell damage. We used JC-1 staining to assess ΔΨ m, which is a marker of mitochondrial oxidative phosphorylation activity.…”
Section: Resultsmentioning
confidence: 88%
“…Intracellular reactive oxygen species (ROS) levels were measured using Image-iT LIVE Green Reactive Oxygen Species Detection Kit (Molecular Probes, Life Technologies Europe BV) as described previously (Suh et al 2010). Briefly, the assay is based on 5-(and-6)-carboxy-2 0 , 7 0 -dichlorodihydrofluorescein diacetate (carboxy-H2DCFDA), a fluorogenic marker that will be cleaved upon the presence of ROS.…”
Section: Measurement Of Intracellular Reactive Oxygen Speciesmentioning
confidence: 99%